(untitled) (Research, Society and Development, 2023)
Immediate actions in the face of Dental Trauma characterize daily challenges to be addressed by the Dental Surgeon, due to the wide variety of traumas to the dental element and the oral cavity as a whole. These procedures often provide rehabilitation, function, aesthetics and well-being to the patient. Objective: To present a literary review regarding the maneuvers and conduct of the dental professional, related to dental and oral traumas common to everyday clinical practice, taking into account the specifications of each trauma, addressing immediate clinical conduct, clinical anamnesis and radiographic protocols and treatments that aim to obtain a positive clinical result. Methodology: This study includes articles related to dental trauma, ranging from immediate management to treatment, from 2002 to 2023, available in the following databases: Scientific Electronic Librany Online (Scielo) and Pubmed, using the descriptors: Dental injuries, tooth fractures and deciduous teeth, as well as their counterparts in English and Spanish. Results: 45 articles were selected that converge and diverge between clinical protocols, immediate management, clinical case reports and studies on the epidemiology and classification of dental trauma. Conclusion: The clinical protocol for different types of dental trauma based on scientific data and academic bases generates positive clinical results.